PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SEKOLAH DASAR NEGERI 90 SINGKAWANG - Dina Meylinda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to: 1) To find out the difference in mathematical problem-solving abilities of grade V students of SDN 90 Singkawang who are taught with the Problem Based Learning model and conventional learning. 2) To determine the improvement of the mathematical problem-solving ability of grade V students of SDN 90 Singkawang using the problem based learning model. 3) To determine the influence of the problem based learning model to mathematical problem-solving skills. The research was conducted in grade IV of SDN 90 Singkawang because students had not yet reached the completion of learning Mathematics. As a solution, the problem based learning model is used, which is real problem-based learning that encourages students to build their own knowledge, develop high-minded, independent, and confident skills. This study uses a quasi-experimental design. It is concluded that learning using the problem based learning model on the ability to solve mathematical problems is effective. Based on the results of the study, it is known that: 1) there are differences in the mathematical problem-solving abilities of grade V students of SDN 90 Singkawang who are taught with the Problem Based Learning model and conventional learning. Based on the results of the Tcount obtained of 5,849 and obtained the Ttable of 2,010, it was found that the Tcount > Ttable was 5,849 > 2,010. 2) there is an improvement in the mathematical problem-solving ability of grade V students of SDN 90 Singkawang using the problem based learning. Based on the results of the N-gain score obtained at 0.58 and obtained an N-gain % of 58% in the medium category. 3) there is an effect of the problem based learning Learning model on mathematical problem-solving ability. Based on the Effect Size of 1.68 and is in the large category.